IS THERE AN ALTERNATIVE TO THE PAY-AS-YOU-GO PENSION SYSTEM IN SERBIA? - Altiparmakov, Nikola (Economic Annals, 2013)
International pension reform experiences indicate that, amid demographic aging, each country needs to identify the reform policies most suited to its own economic and social environment. The economic analysis in this paper suggests that a potential prefunding of the Serbian pension system, either through a public pension reserve fund or mandatory private pension funds, would yield an economic performance inferior to the existing PAYG financing. If a wealth transfer from current to future generations is desirable from the macroeconomic or social perspective it should be implemented through repayment of outstanding public debt, not through pension system prefunding. Pension reform efforts should thus focus on parametric PAYG changes and adequate integration of voluntary retirement saving vehicles into the Serbian pension system.